A new decoupled tangential contouring control scheme for multi-dimensional motion. (September 2020) - Wan, Min; Xiao, Qun-Bao; Liu, Yang; Zhang, Wei-Hong
Abstract: Contour error, which is defined as the distance from the actual tool position to the desired tool trajectory, is directly related to the dimensional precision of the machined parts. In this paper, a new decoupled tangential contouring control scheme (DTCCS), which focuses on directly reducing the contour error, is proposed for multi-dimensional motion. The DTCCS decouples the coupling effect between tangential and contouring error control. Because of this decoupling, the DTCCS realizes controlling the tangential error and the contour error in a separate, independent and time-invariant way. At the same time, various control strategies can be integrated into the DTCCS. The stability of the DTCCS is theoretically proved. Based on the proposed DTCCS, a pole placement tangential tracking error controller and a PID contour error controller are designed and integrated together to implement the DTCCS. Experiments, which are carried out on an in-house developed open architecture CNC machine tool, show that the DTCCS can realize the decoupling of tangential control and contouring control, and can greatly reduce the contour error.